Communication skill assessment form - Md Mustafa, Md Muziman Syah; Ahmad, Norsham (2020)
This communication skill assessment form is developed as a tool to evaluate Optometry students' communication skill during handling and delivering consultation to the patients in Primary Optometry Clinic I, II and III. It provides an assessment rubric to assist a clinical supervisor to grade the students' performance